Niger : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This study focused on the macroeconomic framework, food security needs, implementation of priority investment projects, and domestic petroleum pricing policy. The new fiscal program contains a number of new measures, and it is a precise policy for domestic petroleum pricing. The execution of the revenue mobilization strategy is needed to increase Niger's low revenue-to-gross domestic product (GDP) ratio and to meet the expenditure needs associated with the Millennium Development Goals (MDGs). IMF staff encourages the authorities to activate the pace of structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet